Nucleic Acid Sensing by Toll-Like Receptors in the Endosomal Compartment - Miyake, Kensuke; Shibata, Takuma; Fukui, Ryutaro; Sato, Ryota; Saitoh, Shin-Ichiroh; Murakami, Yusuke (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) respond to pathogen constituents, such as microbial lipids and nucleic acids (NAs). TLRs recognize NAs in endosomal compartments. Structural and functional studies have shown that recognition of NAs by TLRs depends on NA processing by RNases and DNases. DNase II-dependent DNA degradation is required for TLR9 responses to single-stranded DNAs, whereas RNase T2-dependent RNA degradation enables TLR7 and TLR8 to respond to nucleosides and oligoribonucleotides. In contrast, RNases and DNases negatively regulate TLR responses by degrading their ligands. RNase T2 negatively regulates TLR3 responses to degrading the TLR3 ligand double-stranded RNAs. Therefore, NA metabolism in the endosomal compartments affects the endosomal TLR responses. Dysregulation of NA metabolism in the endosomal compartment drives the TLR-dependent pathologies in human diseases.